Analisis Kebijakan Keamanan Maritim Indonesia Di Laut Natuna Utara Dalam Menghadapi Agresivitas China: Perspektif Security Dilemma - Fauzi Afrizal Surbakti; Rendi Prayuda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study analyzes Indonesia’s maritime security policy in the North Natuna Sea in response to China’s assertive actions, particularly its unilateral Nine-Dash Line claim, which contradicts the 1982 UNCLOS. The main research problem addresses how Indonesia formulates and implements its maritime security policy and identifies the factors constraining its effectiveness in safeguarding national sovereignty. The study employs a realist framework with a national security perspective and utilizes the security dilemma theory to explain the action-reaction dynamics between Indonesia and China. The unit of analysis is the state, focusing on Indonesia as the primary actor within the international system. This research adopts a qualitative descriptive method, relying on literature review and policy document analysis to gain an in-depth understanding of maritime security policies within a complex and dynamic international context. The findings reveal that Indonesia implements a dual-track strategy. Internally, it strengthens maritime defense through the establishment of an Integrated TNI Unit, increased patrol operations, and the development of maritime infrastructure. Externally, Indonesia emphasizes legal diplomacy, defense cooperation with strategic partners, and active engagement in regional forums. From a security dilemma perspective, these defensive measures may be perceived by China as offensive actions, potentially escalating regional tensions. Furthermore, several inhibiting factors are identified, including limited defense budgets, the absence of an integrated coast guard institution, and Indonesia’s economic dependence on China. These findings indicate that Indonesia’s maritime security policy operates within a strategic dilemma between maintaining sovereignty and avoiding conflict escalation, thus requiring a balanced, adaptive, and rational policy approach.